Effects of Seeding Rates and Harvesting Period on Yield, Oil and Protein Content and Aflatoxin Incidence in Sesame Seed (Sesamum indicum L.) - Mya Thandar; Ed Sarobol; Jindarath Verawudh; Surapol Chowchong (Agriculture and Natural Resources, 2010)
A field experiment was conducted at the National Corn and Sorghum Research Center, Pak Chong, Nakhon Ratchasima during the 2008 rainy season to investigate the effects of seeding rates and harvesting period on sesame yield, oil and protein content and the incidence of aflatoxin. A split-plot in randomized complete block (RCB) design was used, with seeding rates (4, 6, 8 and 10 kg ha-1) allocated to the main plots and harvesting periods (52, 56 and 60 days after flowering, DAF) assigned to sub-plots with four replications. There were interactions between seeding rates and harvesting periods. Seed yield was significantly affected by both seeding rates and harvesting period. Harvesting at 52 DAF produced higher seed yields at each seeding rate. The mean oil and protein content was 37.46% and 26.36%, respectively. Aflatoxin contamination in seeds was 7.58 ppb, which was less than the 20 ppb maximum limit.